Implementation of the Western Australian Osteoporosis Model of Care: a fracture liaison service utilising emergency department information systems to identify patients with fragility fracture to improve current practice and reduce re-fracture rates: a 12-month analysis - Inderjeeth, C.; Raymond, W.; Briggs, Andrew; Geelhoed, E.; Oldham, D.; Mountain, D. (WILEY, 2018)
© 2018 International Osteoporosis Foundation and National Osteoporosis Foundation Summary: Fracture liaison service linked to an emergency department database effectively identifies patients with OP, improves best practice care, reduces recurrent fractures, and improves quality of life (QoL). The next step is to establish cost-effectiveness. This should be seen as the standard model of care. Introduction: The Western Australian Osteoporosis Model of Care recommends implementation of a fracture liaison service (FLS) to manage patients with minimal trauma fractures (MTFs). This study evaluates the efficacy of a FLS linked to a tertiary hospital emergency department information system (EDIS) in reducing recurrent fractures. Methods: Patients aged = 50 years with MTF identified from EDIS were invited to the FLS. Patient outcomes were compared to routine care (retrospective group—same hospital, and prospective group—other hospital) at 3- and 12-month follow-up. Results: Two hundred forty-one of 376 (64.1%) eligible patients participated in the FLS with 12 months of follow-up. Absolute risk of recurrent MTF at 12 months was reduced by 9.2 and 10.2% compared with the prospective and retrospective controls, respectively. After age/sex adjustment, FLS participants had less MTF at 12 months vs. the retrospective controls, OR 0.38 (95%CI 0.18–0.79), but not the prospective controls, OR 0.40 (95%CI 0.16–1.01). FLS patients were more likely to receive the ‘best practice’ care, i.e. awareness of osteoporosis, investigations, and treatment (all p < 0.05). ‘Fallers’ (OR 0.48 (95%CI 0.24, 0.96)) and fall rates were lower in the FLS (p = 0.001) compared to the prospective control. FLS experienced the largest improvement in QoL from 3 to 12 months as measured by the EuroQoL 5-domain (EQ-5D) UK weighted score (+ 15 vs. - 11 vs. - 16%, p < 0.001) and EQ-5D Health State visual analogue scale (+ 29 vs. - 2 vs. + 1%, p < 0.001). Conclusion: Patients managed in a linked EDIS-FLS were more likely to receive the ‘best practice’ care and had lower recurrent MTF and improved QoL.